ANALISIS POSITIONING DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN I-PHONE PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS ISLAM INDONESIA (UII) YOGYAKARTA - Lukia Zuraida; Dwi Novitasari (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2016)
This research analyzed positioning and brand awareness on decision to purchase i-Phone. The research done in 2013 using 100 students of economic faculties, Universitas Islam Indonesia (UII). The analytical method used was multiple regression. The results showed that a significant differences between positioning with purchasing decisions as indicated by the significance value likewise brand awareness with purchasing decisions. This suggests that positioning and brand awareness variables will be increased purchasing decisions.